Stuber [videorecording (DVD)] - Bautista, David, 1969-; Nanjiani, Kumail; Uwais, Iko, 1983- (Twentieth Century Fox Home Entertainment, 2019)
When a mild-mannered Uber driver named Stu picks up a passenger who turns out to be a cop hot on the trail of a brutal killer, he's thrust into a harrowing ordeal where he desperately tries to hold onto his wits, his life, and his five-star rating.